2022
DOI: 10.3390/microorganisms10010189
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomics of Typical and Atypical Aeromonas salmonicida Complete Genomes Revealed New Insights into Pathogenesis Evolution

Abstract: Aeromonas salmonicida is a global distributed Gram-negative teleost pathogen, affecting mainly salmonids in fresh and marine environments. A. salmonicida strains are classified as typical or atypical depending on their origin of isolation and phenotype. Five subspecies have been described, where A. salmonicida subsp. salmonicida is the only typical subspecies, and the subsp. achromogenes, masoucida, smithia, and pectinolytica are considered atypical. Genomic differences between A. salmonicida subsp. salmonicid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 93 publications
4
22
0
Order By: Relevance
“…salmonicida. Although studies have revealed the difference of ISs between different groups of A. salmonicida, they are limited to a small number of strains or draft genomes (Vasquez et al, 2022;Vincent et al, 2016). This study presents a specific and clear ISs repertoire based on complete genomes of A. salmonicida, and is a good verification and supplement for the existing findings.…”
Section: F I G U R Esupporting
confidence: 51%
See 2 more Smart Citations
“…salmonicida. Although studies have revealed the difference of ISs between different groups of A. salmonicida, they are limited to a small number of strains or draft genomes (Vasquez et al, 2022;Vincent et al, 2016). This study presents a specific and clear ISs repertoire based on complete genomes of A. salmonicida, and is a good verification and supplement for the existing findings.…”
Section: F I G U R Esupporting
confidence: 51%
“…According to the prediction results, the ISs repertoire is also obviously different among three groups of A. salmonicida as proposed in this study, that is, ‘typical psychrophilic’, ‘atypical psychrophilic’ and ‘mesophilic’ group (Figure 3, Figure 5), suggesting that ISs indeed play a major role in the evolution and classification of A. salmonicida . Although studies have revealed the difference of ISs between different groups of A. salmonicida , they are limited to a small number of strains or draft genomes (Vasquez et al, 2022; Vincent et al, 2016). This study presents a specific and clear ISs repertoire based on complete genomes of A. salmonicida , and is a good verification and supplement for the existing findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The taxonomy of A. salmonicida is discussed in another article in the Special Issue by the team of J. Santander [ 7 ]. In this case, the focus is on the analysis of the complete genome of atypical psychrophilic strains.…”
mentioning
confidence: 99%
“…Thus, even though the number of genomes in the databases is increasing, the majority of these are in the form of contigs only. To help to better understand the diversity and pathogenesis, Vasquez et al produced the complete genome of four psychrophilic strains of A. salmonicida , including three with atypical characteristics (J409, J410, J411) [ 7 ]. Obtaining these genomes enabled the authors to make a very detailed analysis of their characteristics, including their phylogeny, chromosome synteny, presence of insertion sequences, virulence and transcriptomic regulation genes, non-coding RNA, and plasmids.…”
mentioning
confidence: 99%